PENGARUH REPUTASI AUDITOR, REPUTASI UNDERWRITER, DAN PERSENTASE FREE FLOAT TERHADAP TINGKAT UNDERPRICING PADA INITIAL PUBLIC OFFERING (Studi Empiris pada Perusahaan yang Go Public di Bursa Efek Indonesia Periode Tahun 2012-2014) - Eliezer Kurnia Aryapranata; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2017)
Underpricing is a phenomenon that occurs when the stocks price at primary market was lower than the stock's closing price on the first day at the secondary market. This study aims to analyze the effect of auditor reputation, underwriter reputation, and the percentage of shares offered to the public (free float) toward level of underpricing on initial public offering (IPO) at Indonesia Stock Exchange in 2012 to 2014.This study used data of the 61 companies in Indonesia that were found to be underpriced when conducted IPO in 2012 to 2014 as the sample which was obtained by purposive sampling method. The type of data is secondary data which were collected by documentation method. The research used multiple linear regression as data analysis technique.The result of this study indicates that partially auditor reputation variable and underwriter reputation variable have significant and negative effect on the level of underpricing. While the percentage of free float variable has insignificant effect on the level of underpricing but the coefficient direction is positive. Simultaneously, the auditor reputation variable, underwriter reputation variable, and the percentage of free float variable have significant effect on the level of underpricing.